Peningkatan Kemampuan Membaca Permulaan Siswa Kelas 1 SDN NEGLA 02 Melalui Media Kartu Huruf Kecamatan Losari - Rohanah Rohanah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
The purpose of the research to be achieved is to find out whether letter card media can improve early reading skills in class I SDN Negla 02, Losari District, Brebes Regency. The variable that became the target of change in this classroom action research was to improve the early reading ability of first grade elementary school students, while the action variable used in this study was letter card media. This Classroom Action Research was carried out in two cycles with a total of 25 students, each cycle consisting of action planning, observation and reflection. From the results of the first cycle of action, the students' reading learning outcomes were obtained with an average value of 69 with a student percentage of 52%. The results of the second cycle of action obtained the results of students' early reading learning with an average value of 78.67 with a student percentage of 92%. Thus, it can be concluded that learning Indonesian (preliminary reading) with the use of letter card media can improve early reading skills in grade I SD Negeri Negla 02, Losari District, Brebes Regency.